2008
DOI: 10.1099/mic.0.2008/019836-0
|View full text |Cite
|
Sign up to set email alerts
|

Picocyanobacterial community structure of freshwater lakes and the Baltic Sea revealed by phylogenetic analyses and clade-specific quantitative PCR

Abstract: Phylogenetic relationships among picocyanobacteria from the Syn/Pro clade sensu Sá nchez- Baracaldo et al. (2005) were determined using small subunit (ssu) rDNA sequences from novel culture isolates together with environmental samples from the Baltic Sea and seven freshwater lakes. The picocyanobacterial community comprised members of previously identified clades and of two previously undescribed clades. The number of well-supported clades suggests that freshwater picocyanobacterial communities encompass much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
70
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(75 citation statements)
references
References 43 publications
4
70
1
Order By: Relevance
“…This could be the result of differences in the specificity of the two primer sets that may result in the preferential amplification of taxa (Sipos et al, 2007). We cannot rule out the possibility that the members of group C were presented among the 16S rDNA clones (one of the ungrouped sequences), but they cannot be clearly assigned to this group since no 16S rDNA sequences are available to date from group C. We should emphazise that genetic composition of picocyanobacteria could also have an annual cycle in freshwater ecosystems with the periodic dominance of certain phylotypes (Becker et al, 2007;Ivanikova et al, 2007;Sa´nchez-Baracaldo et al, 2008). Therefore it is likely that the groups reported here as major types of picocyanobacteria have only seasonal dominance in Lake Fertő in the open water.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This could be the result of differences in the specificity of the two primer sets that may result in the preferential amplification of taxa (Sipos et al, 2007). We cannot rule out the possibility that the members of group C were presented among the 16S rDNA clones (one of the ungrouped sequences), but they cannot be clearly assigned to this group since no 16S rDNA sequences are available to date from group C. We should emphazise that genetic composition of picocyanobacteria could also have an annual cycle in freshwater ecosystems with the periodic dominance of certain phylotypes (Becker et al, 2007;Ivanikova et al, 2007;Sa´nchez-Baracaldo et al, 2008). Therefore it is likely that the groups reported here as major types of picocyanobacteria have only seasonal dominance in Lake Fertő in the open water.…”
Section: Discussionmentioning
confidence: 99%
“…3 and 4). Although group B and group C picocyanbacteria seemed to have limited distribution (Robertson et al, 2001;Ernst et al, 2003), increased picoplankton investigations revealed a more widespread occurrence of these groups (Crosbie et al, 2003;Ivanikova et al, 2007;Haverkamp et al, 2008;Sa´nchez-Baracaldo et al, 2008;this study). This widespread dispersal of some closely related picocyanobacterial phylotypes may confirm the high adaptive potential of these groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The information given by ITS fragment length varies among taxa so that Pcy microdiversity can be studied with ARISA to identify different ecotypes, even if the data obtained are not quantitative (Brown et al 2005). A rapid succession of individual Pcy clades, illustrating the patchy structure of the Pcy community, was described over a quite small spatial/temporal scale for lakes in the English Lake District using quantitative PCR (Sánchez-Baracaldo et al 2008). Although we did not perform quantitative PCR, we still obtained a fairly detailed picture of OTU succession in Lake Maggiore.…”
Section: Picocyanobacteria Seasonal Successionmentioning
confidence: 99%
“…Molecular analysis of 16S rRNA genes has resulted in the division of picocyanobacteria into several marine and freshwater clusters (Herdman et al, 2001). Among them, cosmopolitan and unique clusters and sequences have been identified (Crosbie et al, 2003a;Haverkamp et al, 2008;Sánchez-Baracaldo et al, 2008;Jasser et al, 2011), although the ecophysiological differences between strains belonging to various clusters often remain uncharacterized.…”
Section: Introductionmentioning
confidence: 99%